Influence of low-level fall supplementation with a self-fed, high-protein supplement and level of winter supplementation on performance of beef cows grazing tallgrass-prairie range - Wickersham, T.A.; Cochran, R.C.; Dhuyvetter, D.V.; Farmer, C.G.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine the effect of providing a small amount of a high-protein supplement during the fall and effects of increasing subsequent level of winter supplementation on cow-calf performance. One hundred-sixty spring-calving Hereford × Angus cows grazing tallgrassprairie range were used. During the fall, cows either had access to a self-fed, highprotein supplement (30% CP) or were not supplemented. During the winter, range cubes (20% CP) were fed at a daily equivalent of 1, 2, 3, or 4 lb/head and all cows had access to the same self-fed supplement used during the fall period. Cumulative performance (as measured by changes in body condition score and body weight) tended to show limited response to low-level fall supplementation, but was significantly improved as level of winter supplementation increased.
Keywords: Beef; Protein; Range; Beef cattle; Supplementation; Self-feeding